Enhanced Thermoelectric Properties of Cu2SnSe3 by (Ag, In)‐Co‐Doping. (21st June 2016) - Li, Yuyang; Liu, Guanghua; Cao, Tengfei; Liu, LiMin; Li, Jiangtao; Chen, Kexin; Li, Laifeng; Han, Yemao; Zhou, Min
Abstract : Dense bulk samples of (Ag, In)‐co‐doped Cu2 SnSe3 have been prepared by a fast and one‐step method of combustion synthesis, and their thermoelectric properties have been investigated from 323 to 823 K. The experimental results show that Ag‐doping at Cu site remarkably enhances the Seebeck coefficient, reduces both electrical and thermal conductivities, and finally increases the figure of merit (ZT) value. The ZT of the Cu1.85 Ag0.15 SnSe3 sample reaches 0.80 at 773 K, which is improved by about 70% compared with the unadulterated sample (ZT = 0.46 at 773 K). First principle calculation indicates that Ag‐doping changes the electronic structure of Cu2 SnSe3 and results in larger effective mass of carriers, thus enhancing the Seebeck coefficient and reducing the electrical conductivity. The low electrical conductivity caused by Ag‐doping can be repaired by accompanying In‐doping at Sn site, and by (Ag, In)‐co‐doping the thermoelectric properties are further promoted. The (Ag, In)‐co‐doped sample of Cu1.85 Ag0.15 Sn0.9 In0.1 Se3 shows the maximum ZT of 1.42 at 823 K, which is likely the best result for Cu2 SnSe3 ‐based materials up to now. This work indicates that co‐doping may provide an effective solution to optimize the conflicting material properties for increasing ZT. Abstract : By (Ag, In)‐co‐doping, the electrical and thermal properties of Cu2 SnSe3 are concurrently optimized, resulting in increased power factor, reduced thermal conductivity, and greatly enhanced figure of merit, ZT. The ZT of Cu1.85 Ag0.15 Sn0.9 In0.1 Se3 reaches 1.42 at 823 K, which is likely the best result for Cu2 SnSe3 materials. The co‐doping strategy may provide a solution for concurrent optimization of the conflicting transport properties for improving thermoelectric performance.